THE EFFECTIVENESS OF INTERNAL AUDIT IN ENHANCING CORPORATE GOVERNANCE IN IRAQ - Hamza Kadhim Rishag; Mawj Abbas Jasim (American Journals, 2022)
I aimed this is the study to me Determine nature Censorship internal and governance companies From destination consideration Academy And its importance for owners interest.and study nature Relationship between audit external and reinforcement Exercise governance companies and specify Bezel effectiveness audit procedure in Strengthen governance companies in Iraq. used the study curriculum descriptive Analytical.And I concluded the study to me Presence Effect The indication Statistic to effect audit procedure From Before auditors internals on me Investigation governance companies in comp manufacturing the public in Iraq.From hand other , ranges average Arithmetic To measure Effect proces audit procedure on me governance in companies that included the study , Which comp Produce General in Iraq , From2.25to me1.47, and volume the influence From0.699to me0.916, Which.Average to me big , Than Indicates to me direction Imagine the sample Toward Investigation Dimensions audit procedure which Include:(planning , time and scope Review , statement Risks Finance , scale down Cost proces Review)to effect internal.audit in Management companies that included the study.and this is indicative on me effectiveness audit procedure in the influence on me Administration in comp manufacturing the public Iraqi , With what goes along with Imagine a sample search.
Keywords: The effectiveness, Internal audit, enhancing corporate, governance in Iraq, corporate sector.